Students' Challenges and Approaches to Comprehending the TOEFL Reading Section - Aeni, Nur (International Journal of Education Research and Development, 2024)
The TOEFL Reading Section presents a number of challenges for students, ranging from advanced vocabulary to dense academic passages to time management pressures. This abstract presents both the general obstacles faced by students when attempting to comprehend TOEFL reading tasks and those particular approaches that they apply to overcome these difficulties. This is a descriptive qualitative research.  Twenty-two of 7th semesters in English language education study program who enrolled in the TOEFL preparation class batch 7 were selected purposively to be the respondents of this study.  The instrument is in depth interview. Then the result of the interview was analyzed by contextual Analysis: Analyze how these themes emerge in different contexts or situations. Pay attention to nuances, such as differences between demographic groups, changes over time, or situational factors that might affect responses. The paper, based on the literature review and student feedback review, emphasizes strategic reading approaches-such as skimming, scanning, and making inferences-to enhance comprehension. Regular practice and resources outside of class, such as vocabulary-building tools and online reading comprehension exercises, are also emphasized. Results showed that students who have more actively practiced these strategies have increased their comprehension and time efficiency, and therefore did better on the TOEFL reading. This study emphasizes the importance of targeted instructional support in preparing students for the TOEFL in their acquisition of not only the requisite skills but also the self-confidence to succeed.